THE «THREE SISTERS» IN MODERN HUMAN NUTRITION AS AN INNOVATIVE INTEGRATION OF TRADITION, SCIENCE, AND BUSINESS - Adamchuk-Chala, Nadiia; Yefymyshch, Nadezhda; Chala, Yelyzaveta (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2025)
This paper explores the agroecological, cultural, nutritional, and business-related significance of the «Three Sisters» intercropping system - corn, beans, and squash-rooted in Native American agricultural traditions. By analyzing scientific studies and meta-analyses, the authors assess how this system enhances land-use efficiency, soil health, pest resistance, and dietary quality. The study highlights the potential of combining traditional knowledge with modern science and entrepreneurial strategies to advance sustainable food systems, support Indigenous food sovereignty, and create business opportunities in local and global agri-food markets. It also addresses challenges such as reconciling cultural and scientific paradigms and land accessibility.